Cultural traductological analysis in translation. On the material of culturemes in Rudin, by Iván Turguéniev and its translation into Spanich (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
In the first part of this article, the nature of so-called culturemes is studied, understood as semiotic units referring to an element belonging to a given culture which is unknown or without an exact equivalent in other cultures, and which is therefore perceived as a cultural specificity. Additionally, criteria are examined for both their traditional classification by referential content, and their classification by semiotic relevance in a translation. In the second part, the cultural-traductological method is used to analyse culturemes present in Rudin, the work by Iván Turguéniev, and the way of transposing these in the different Spanish versions by different translators.
Keywords: Traductology; culturology; cultureme; cultural-traductological method; Iván Turguéniev; Rudin; russian language; spanish language